Pengaruh Metode Mind Mapping terhadap Kemampuan Berpikir Kritis dan Prestasi Belajar PAI Siswa Kelas VII SMPN 1 Slahung - Taufik Arrohman (An-Nahdhah: Journal of Education and Culture, 2025)
This research was motivated by the lack of innovation and creation of PAI learning methods, which was caused by the age factor of PAI teachers, as well as the minimal budget allocated for learning media by schools. So this has implications for low critical thinking skills and learning achievement in PAI learning, for class VII students at SMPN 1 Slahung. The aim of this research is to describe the implementation of the mind mapping learning method in PAI learning activities in class VII of SMPN 1 Slahung, as well as to analyze the ratio of increasing critical thinking skills and PAI learning achievement for class VII students of SMPN 1 Slahung after using the mind mapping learning method. The research method used is a quantitative experimental approach. Data collection techniques use observation, interviews, critical thinking ability tests, and documentation. The results of this research show that the learning process between the control class (VII B) and the experimental class (VII C) was carried out in the same flow, starting from the learning material, types of questions and time allocation for test instruments, and allocation of learning hours. The difference lies in the use of the lecture method in the control class, and the mind mapping method in the experimental class. The results of this research show that the use of the mind mapping learning method can improve critical thinking skills and student learning outcomes, between the experimental class (VII C) and the control class (VII B). The final results of the calculation show that |t_count|>t_table, then there is a significant difference in the average score between the experimental class post test (89.40), better than the control class post test (76.77).